2013
DOI: 10.1007/s10530-013-0575-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dreissena fouling on the physiological condition of native and invasive bivalves: interspecific and temporal variations

Abstract: The impact of Dreissena fouling on unionids has hardly been studied in Europe, despite the fact that in some ecosystems (e.g. Lake Balaton, Hungary) infestations of several hundreds to a thousand individuals per unionid have been observed. At present, the zebra mussel Dreissena polymorpha is a dominant species in Lake Balaton and in the last decade three other invasive bivalves were introduced, potentially increasing the pressure on native unionid survival. We examined whether the fouling of dreissenids (zebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 53 publications
0
21
1
1
Order By: Relevance
“…The effect of burrowing depth has been supported by Bódis et al. (), who found no differences in fouling intensity among unionid species after controlling for shell area. However, the better settlement of dreissenids on A. anatina and S. woodiana compared to Unio spp.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The effect of burrowing depth has been supported by Bódis et al. (), who found no differences in fouling intensity among unionid species after controlling for shell area. However, the better settlement of dreissenids on A. anatina and S. woodiana compared to Unio spp.…”
Section: Discussionmentioning
confidence: 74%
“…individuals, compared to Anodonta and Sinanodonta sp. (Bódis et al., ). Alternatively, particularly in the case of A. cygnea , this may also suggest the active avoidance by zebra mussels, which relatively more often attached to conspecifics.…”
Section: Discussionmentioning
confidence: 99%
“…It is relevant to note that bottom topography, oscillatory flows, and interactions among exhalant jets may also influence mixing (O'Riordan et al, ; Folkard and Gascoigne, ). Regardless, these results demonstrate that dreissenid mussels use a diverse set of exhalant behaviors, which lead to different levels of local mixing that may support higher productivity and may help to explain their large impacts on aquatic ecosystems (Schloesser et al, ; Bódis et al, ).…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, infestation of unionids by Dreissena mussels in the Detroit River resulted in a drop in species richness from 26 to 5 native species during the 1990s (Schloesser et al 1998(Schloesser et al , 2006. However, Sousa et al (2011) and Bódis et al (2013) reported negative impacts of the zebra mussel on the physiological condition of native unionids in Europe. Although dramatic decline of unionids has been reported in some Belarus lakes shortly after zebra mussel introduction (e.g.…”
Section: Introductionmentioning
confidence: 99%